1999
DOI: 10.1046/j.1365-2265.1999.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo study of the cortisol–cortisone shuttle in subcutaneous abdominal adipose tissue

Abstract: We have demonstrated 11 beta-HSD oxo-reductase activity in subcutaneous abdominal adipose tissue, which may be increased in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 24 publications
4
34
0
3
Order By: Relevance
“…Cell culture media and reagents for reverse transcription of RNA were from Invitrogen (Carlsbad, CA), [1,2,6, H]-cortisol from Amersham Bioscience (Piscataway, NJ), [1,2,6, H]-cortisone from American Radiolabelled Chemicals (St. Louis, MO), the SV total RNA isolation system from Promega (Madison, WI) and reagents for TaqMan realtime PCR from Applied Biosystems (Foster City, CA). Monoclonal antibodies were from Roche Diagnostics (Rotkreuz, Switzerland) and fluorescent antibodies from Molecular Probes (Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture media and reagents for reverse transcription of RNA were from Invitrogen (Carlsbad, CA), [1,2,6, H]-cortisol from Amersham Bioscience (Piscataway, NJ), [1,2,6, H]-cortisone from American Radiolabelled Chemicals (St. Louis, MO), the SV total RNA isolation system from Promega (Madison, WI) and reagents for TaqMan realtime PCR from Applied Biosystems (Foster City, CA). Monoclonal antibodies were from Roche Diagnostics (Rotkreuz, Switzerland) and fluorescent antibodies from Molecular Probes (Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
“…11b-HSD1 is a bidirectional enzyme, catalysing both oxidation and oxoreduction with comparable efficiencies in cell lysates, whereby oxoreduction is less stable and decreases upon preparation of microsomes and purification [2]. Experiments in animals and humans indicated that 11b-HSD1, which is highly expressed in liver and adipose tissue [1] and has been associated with obesity and type 2 diabetes mellitus [3], is predominantly an oxoreductase in vivo [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In biopsies, it has not been possible to correlate 11HSD1 activity or mRNA with cortisol levels or mRNA levels for glucocorticoid-dependent genes (21,22). Previous attempts to measure adipose 11HSD1 in vivo using arteriovenous sampling across abdominal subcutaneous adipose tissue have been inconclusive, perhaps because of variability in measurement (26). Recently, we (27) and others (28) have validated a new approach using deuterated cortisol tracer infusion to measure the turnover of 11HSD activities in vivo.…”
mentioning
confidence: 99%
“…The distribution of 11β HSD-1 expression is similar in mice and humans. In vivo measurements using arteriovenous sampling have shown that cortisone is converted into cortisol in human liver [12] and subcutaneous adipose tissue [13], and 11β HSD-1 is the only human enzyme known to catalyse this reaction. Inhibition of 11β HSD-1 with the non-selective inhibitor carbenoxolone results in enhanced insulin sensitivity in the liver [14,15], consistent with the effects of a more selective 11β HSD-1 inhibitor in mice [9,10].…”
mentioning
confidence: 99%